Is Application of Uterine Fundus Pressure with a Sandbag Effective in Reduction of Cesarean Bleeding? A Prospective Case Control Study - Pala, Sehmus; Atilgan, Remzi; Yurt, Nurdan; Keser, Hasan Burak; Oglak, Sueleyman Cemil; Yilmaz, Mustafa (Imr Press, 2023)
Background: Uterine compression methods reduce the amount of postpartum bleeding. In our study, we investigated the effect of fundal pressure, which will be created by a sandbag placed on the abdomen, on reducing post-cesarean bleeding. Methods: A total of 482 patients who delivered by cesarean section (CS) in the Obstetrics Clinic of Firat University Faculty of Medicine between January 2021 and December 2021 were included in this prospective, randomized, single-center study. There were two groups: control group (n = 246), weighted group (n = 236). A sandbag weighing approximately 3 kg was used as a fundal compression tool. Hemoglobin (Hb) and hematocrit (Hct) concentrations and amount of vaginal bleeding were determined preoperatively and at the postoperative 8th and 24th hours. In addition, the time of milk coming from the breast and visual analogue scale (VAS) were evaluated. Results: The postoperative Hb value at 24 hours was significantly lower in weighted group compared to control group. The estimated amount of postoperative bleeding (based on the number of pads) was higher in weighted group compared to control group. The time to onset of milk production from the breast at the postoperative 8th hour was significantly longer in weighted group compared to control group. Postoperative VAS scores at 24 hours were significantly higher in weighted group compared to control group. Conclusions: Applying fundal pressure by using a sandbag from the abdominal route seems ineffective in reducing the amount of bleeding after CS. It may even increase the amount of bleeding. Clinical Trial Registration: The study was registered at https://clinicaltrials.gov/, registration number: NCT06005831.
Keywords: cesarean section; fundal pressure; postpartum hemorrhage; sandbag